Case Report: Identification of a rare nonsense mutation in the POC1A gene by NGS in a diabetes mellitus patient - Li, Dongfeng; Li, Shihui; Zhou, Jingjing; Zheng, Lili; Liu, Gui; Ding, Chengzhang; Yuan, Xingyun (Frontiers in Genetics, 2023)
Objective: This study aimed to investigate the clinical and molecular biology of a patient with a type of diabetes mellitus caused by a mutation in the POC1A(OMIM number: 614783) gene and explore its pathogenesis and related characteristics. Methods:The patient was interviewed about his medical history and subjected to relevant examinations. Blood DNA samples were collected from the patient and his family members (parents) for trio whole-exome sequencing. Whole-exome sequencing was performed using the IDT xGen Exome Research Panel v1.0 whole-exome capture chip and sequenced using an Illumina NovaSeq 6000 series sequencer(PE150);the sequencing coverage of the target sequence was not less than 99%.After systematic analysis and screening of the cloud platform for accurate diagnosis of genetic diseases,which integrated molecular biology annotation,biology,genetics, and clinical feature analysis,combined with a pathogenic mutation database, normal human genome database, and clinical feature database of 4,000 known genetic diseases,hundreds of thousands of gene variants were graded using the gene data analysis algorithm,a three-element grading system, and the American Society of Medical Genetics gene variant grading system. After polymerase chain reaction testing,the target sequence was verified by Sanger sequencing using an ABI3730 sequencer, and the verification result was obtained using sequence analysis software. Results:The patient had a peculiar face,a thin body,and a body mass index of 16.0kg/m2.His fasting connecting peptide was 10.2ug/L,his fasting insulin was 44mIU/L, his fasting blood glucose was 10.5mmol/L, and his glycosylated haemoglobin was 12.5%.After hospitalisation, the patient was given 0.75g/d metformin tablets and 15mg/d pioglitazone dispersible tablets, and his fasting blood glucose reduced to 9.2mmol/L. After 48U/L insulin treatment, the patient’s fasting blood glucose was reduced to 8.5 mmol/L. Genetic screening revealed that there was a pathogenic variant at the POC1A gene locus and a cytosine-to-thymine mutation at the G81 locus, turning the Arg to a termination codon and shortening the POC1A protein from 359 amino acids (aa) to 80 aa. No mutation was detected in the patient’s parents’ POC1A gene loci. Conclusion:The patient’s diabetes was caused by a POC1A gene mutation at the G81 locus, which is rarely reported in the clinic. The specific manifestations of this mutation need to be further investigated.